2016
DOI: 10.15232/pas.2016-01539
|View full text |Cite
|
Sign up to set email alerts
|

Management characteristics of beef cattle production in the Northern Plains and Midwest regions of the United States

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…For example, both Nebraska and Colorado had substantial corn residue utilization (∼52 and 56% of their total corn hectares being grazed) through regionalized integration (Schmer et al, 2017). Another survey indicated that grazing of crop residue within farm systems was reported by about 70% of farmers in the U.S. NGP (Asem‐Hiablie et al, 2016). A survey of South Dakota commodity crop producers indicated that 55% of farmers use ICLSs, of which 22% adopted these practices within the last 10 yr (J.D.…”
Section: Background and Historymentioning
confidence: 99%
“…For example, both Nebraska and Colorado had substantial corn residue utilization (∼52 and 56% of their total corn hectares being grazed) through regionalized integration (Schmer et al, 2017). Another survey indicated that grazing of crop residue within farm systems was reported by about 70% of farmers in the U.S. NGP (Asem‐Hiablie et al, 2016). A survey of South Dakota commodity crop producers indicated that 55% of farmers use ICLSs, of which 22% adopted these practices within the last 10 yr (J.D.…”
Section: Background and Historymentioning
confidence: 99%
“…When extrapolating these data to other production systems and regions, importance will vary among the metrics considered. For example, some regions (Midwest and Eastern USA) are wetter than others (Western USA) and thus require less water use; however, leaching and runoff of nutrients are higher for the former (Asem-Hiablie et al 2015, 2016, 2017. In regions with large dairy herds where cull dairy calves are incorporated into the beef herds, allocation of impacts of the breeding herd to dairy reduces the environmental footprints of the beef produced (Capper 2011;Stackhouse-Lawson et al 2012;.…”
Section: Impact Reduction Opportunitiesmentioning
confidence: 99%
“…For consistency, operation types follow previous definitions given by Asem-Hiablie et al (2016). A ranch is defined as an operation that predominately includes cattle on pasture or rangeland.…”
Section: Methodsmentioning
confidence: 99%